Transcriptomics of Marburg virus-infected primary proximal tubular cells reveals negative correlation of immune response and energy metabolism - Koch, Benjamin; Filzmayer, Maximilian; Patyna, Sammy; Wetzstein, Nils; Lampe, Sebastian; Schmid, Tobias; Geiger, Helmut; Baer, Patrick C.; Dolnik, Olga (Virus research, 2024)
•Marburg virus infects and replicates in primary human proximal tubular cells (PTC).•Transcriptome analyses at multiple time points revealed a profound inflammatory response by IFNα, -y and TNFα signaling.•Among the strongly downregulated gene sets were targets of the transcription factors MYC and E2F, the G2M checkpoint, as well as oxidative phosphorylation.•Importantly, the downregulated factors comprise PGC-1α, a key factor in mitochondrial biogenesis and renal energy homeostasis, to be substantially downregulated in MARV-infected PTC.•Our results suggest inflammation-induced changes in tubular energy metabolism as a possible factor in MARV-associated tubular dysfunction. Marburg virus, a member of the Filoviridae, is the causative agent of Marburg virus disease (MVD), a hemorrhagic fever with a case fatality rate of up to 90 %. Acute kidney injury is common in MVD and is associated with increased mortality, but its pathogenesis in MVD remains poorly understood. Interestingly, autopsies show the presence of viral proteins in different parts of the nephron, particularly in proximal tubular cells (PTC). These findings suggest a potential role for the virus in the development of MVD-related kidney injury. To shed light on this effect, we infected primary human PTC with Lake Victoria Marburg virus and conducted transcriptomic analysis at multiple time points. Unexpectedly, infection did not induce marked cytopathic effects in primary tubular cells at 20 and 40 h post infection. However, gene expression analysis revealed robust renal viral replication and dysregulation of genes essential for different cellular functions. The gene sets mainly downregulated in PTC were associated with the targets of the transcription factors MYC and E2F, DNA repair, the G2M checkpoint, as well as oxidative phosphorylation. Importantly, the downregulated factors comprise PGC-1α, a well-known factor in acute and chronic kidney injury. By contrast, the most highly upregulated gene sets were those related to the inflammatory response and cholesterol homeostasis. In conclusion, Marburg virus infects and replicates in human primary PTC and induces downregulation of processes known to be relevant for acute kidney injury as well as a strong inflammatory response.